A "special ingredient": development of an intervention to implement structured and collaborative clinical planning processes for Comprehensive, High-dose Aphasia Treatment (CHAT). - Levine, Rachel; Dignam, Jade; McSween, Marie-Pier; Hill, Annie; Copland, David; Shrubsole, Kirstine (Disability & Rehabilitation, 2026)
Purpose: Intensive Comprehensive Aphasia Programs (ICAPs) deliver personalised treatment to improve outcomes for people with aphasia. Structured, collaborative clinical planning may address challenges associated with personalising therapy, facilitating implementation of these programs. This study aimed to (1) understand speech pathologists' perspectives of barriers, facilitators, and strategies to implementing clinical planning for one modified ICAP, Comprehensive, High-dose Aphasia Treatment (CHAT), and its telerehabilitation-delivered counterpart (TeleCHAT); and (2) develop a theory-driven intervention to implement clinical planning. Methods: Phase one: treating speech pathologists and speech pathology leaders involved in CHAT/TeleCHAT participated in focus groups/interviews. Reported barriers, facilitators, and strategies for implementation were analysed via mixed deductive-inductive content analysis and categorised using implementation frameworks. Phase two: findings from phase one were translated into an implementation intervention using determinant-strategy mapping tools. Results: Three themes were identified: (1) overall experience; (2) learning a new way of practice; and (3) the implementation context. Clinical planning was highly regarded by participants. However, barriers relating to its fit within a clinical setting were reported. Adequate social support may leverage this barrier. An implementation intervention including six evidence-based strategies was developed. Conclusions: Strategies to support implementation of clinical planning for CHAT/TeleCHAT have been identified, an important preliminary step for implementing ICAPs. IMPLICATIONS FOR REHABILITATION: Aphasia is a language disorder which commonly occurs post-stroke and patients with aphasia experience poorer quality of life than any other health condition. Personalising evidence-based treatments is an important but clinically challenging component of Intensive, Comprehensive Aphasia Programs (ICAPs), a contemporary and effective model of care. Structured and collaborative processes for explicit treatment planning may support speech pathologists to deliver personalised aphasia therapy. This research identified barriers, facilitators, and potential strategies for the implementation of structured and collaborative clinical planning for a modified ICAP, to support the translation of these programs in practice.